L’imagerie irlandaise, du stéréotype au simulacre - Corinne Feïss-Jehel; Pierre-Jérôme Jehel (Projets de Paysage)
Landscapes and the images of them which are produced, broadcast or marketed, occupy a privileged place in the Irish tourist industry. We will approach these representations through advertising images and personal photographs. “Contrasting Lands” (in French, “Terres de constraste”) are pictures accompanied by advertising messages and representations. The world thus photographed presents a series of stereotypes through which we will travel during our visit. Landscaping developments are now creating a museography of territories which corresponds to these stereotypes. In this article we will discuss the invention of some of these closed worlds in Ireland, imitations of reality which are transformed into visual consumer goods. Historical reconstructions — the murals of Derry or Belfast, the new areas within the district of Titanic, and popular history — play a major role in these choices.